Rancang Bangun Inventory System Menggunakan Model Waterfall Berbasis Website - Gede Pratama Pinatih (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Information Technology has experienced a significant increase in various human lives, especially in the field of goods sales industry. Information Technology has a very important role in changing the manual process into a computerized one that functions in processing data and converting data to obtain accurate information. This proves that Information Technology has a very important role because it is a solution to gain an advantage in business competition. CV. Dewi Laksmi is a convection industry that produces apparel such as shirts, t-shirts, PDH), PDL, pants, and jackets according to customer orders. In the transaction process and recording the sale of goods on the CV. Dewi Laksmi still uses manual methods using books and calculators as tools for calculating. Therefore, the Inventory Information System is needed by CV. Dewi Laksmi to run business processes and is able to provide accurate information. A website-based inventory system designed using Waterfall as a design method by applying the Hypertext Preprocessor programming language and database using My Structured Query Language. This Goods Inventory System is expected to generate information automatically quickly and accurately which can result in misinformation.